"Workers' strikes and collective bargaining: a study of the SAMWU municipal worker strike of 2018, Port Elizabeth, South Africa" - Gumbo, Eugene (Rhodes University, Faculty of Humanities, Department of Sociology, 2020)
The focus of this study centered on investigating the perceptions and opinions surrounding the eruption of strike action and its effectiveness during a collective bargaining process. The case study employed was the 2018 municipal strike in Port Elizabeth, organised by the South African Municipal Workers Union (SAMWU). A Marxist theoretical framework was chosen for this study. It argues that strike action is a means through which workers communicate their dissatisfaction or enforce particular demands, with trade unions playing a protagonist's role. Strike action, generally, is caused by a plethora of reasons ranging from disciplinary issues and conditions and hours of work, to be mention a few. However, the major force behind strike eruption is the wage agenda, as workers are always striving to get better wages while employers, on the other hand, attempt to reduce them so as to increase profits. South Africa has had its fair share of municipal strike action ever since the apartheid period, the early stages of democracy up to the contemporary times of the 21st century with various strategies, successes and losses being experienced. Democracy in South Africa also saw some developments in the labour sphere in relation to statutes surrounding strike action. The LRA and the Constitution of South Africa inform the right to strike and offer guidelines as well as consequences that steer strike action in a direction that does not jeopardize the workers, employers and the general public. The research found that workers do understand what strike action is, its causes and its various implications. Furthermore, it was discovered that this worker tool has been successful in putting pressure on the negotiation process as well as luring employers back to the negotiation table, for example. However, it was also uncovered that there are present, factors that hampered the impact of strike action during the bargaining procedure in focus. These are namely, the political institutionalization of trade unions, ill-equipped union leaders, a reluctance to implement strike agreements by employers, the use of violence by municipal workers during the strike, to mention but a few. Therefore, when looking at the strike in question, the effectiveness of strike action during the collective bargaining process was found to be easily contestable.
Keywords: South African Municipal Workers Union; Strikes and lockouts -- Municipal government -- South Africa -- Port Elizabeth; Collective bargaining -- Municipal employees -- South Africa -- Port Elizabeth; Philosophy, Marxist; Labor unions -- South Africa; Labor unions -- Law and legislation -- South Africa; Industrial relations -- South Africa -- Port Elizabeth